PERLINDUNGAN HUKUM TERHADAP NASABAH KORBAN KEJAHATAN PENGGANDAAN KARTU ATM PADA BANK SWASTA NASIONAL DI DENPASAR - Juniawan, Komang (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 2 (2013)DO - 10.24843/JMHU.2013.v02.i02.p07, 2013)
Responsibility of the bank to refund customers money that became victims of ATM card duplication is the bank have responsibility to refund the customer money, so that the loss of customer funds was caused by his own negligence, then the bank is not have responsibility to refund losses suffered by customers. Legal efforts taken by the bank to refund customers money that became victims of ATM card duplication such as : Clarification of customer complaints by checking the data to determine the customer's account transactions that cause a reduction in the customer's account balance, then deliver customer transactions was conducted customer; Checking customer transactions allegedly clumsy, one of which is checking the CCTV at the cash machine withdrawals are not recognized by the customer, checking and known whether the transaction is concluded that the transaction is correct or odd transactions; Returns missing customer funds, if it is concluded that the clients do not make transactions recorded in the customer's account, and making a crime report in the ATM card duplication police to do the investigation against the perpetrators
Keywords: Customer protection, the trust relationship between the bank and its customers and the bank' s responsibility to customers